Do introduced apex predators suppress introduced mesopredators? A multiscale spatiotemporal study of dingoes and feral cats in Australia suggests not. Issue 12 (16th October 2019) - Fancourt, Bronwyn A.; Cremasco, Peter; Wilson, Cameron; Gentle, Matthew N.
Abstract: The role of apex predators in structuring ecosystems through the suppression of mesopredator activity and abundance is receiving increasing attention, largely due to the potential benefits for biodiversity conservation. In Australia, invasive mesopredators such as feral cats ( Felis catus ) have been identified as major contributors to Australia's mass mammal extinctions since European arrival. The introduced dingo ( Canis familiaris ) has been proposed as a novel way to suppress the impacts of feral cats, however, scientific evidence of the dingo's suppressive role is equivocal. We used camera traps to investigate whether a large introduced predator (dingo) suppresses the activity of an established introduced mesopredator (feral cat) across a national park site conserving endangered species, and an agricultural site supporting cattle grazing enterprises. Feral cats and dingoes exhibited marked overlap in both temporal and spatial activity, indicating coexistence. Some temporal separation was evident at the agricultural site, however, this reflected higher diurnal activity by dingoes, not a responsive shift in cat activity. Cat activity times were unrelated to dingo presence and did not differ between areas occupied by dingoes and dingo‐free areas. There was no evidence of dingoes excluding cats from patches at either site, nor was there evidence of within‐night fine‐scale spatiotemporal avoidance of dingoes by cats. Species co‐occurrence models revealed dingoes had no negative effect on the probability of cat presence. The probability of detecting a cat on the national park was significantly higher in areas with dingoes than in dingo‐free areas, while on agricultural land, cat detectability did not differ between areas with and without dingoes. Cats remained active, abundant and widespread across both sites, with evidence of cats hunting and breeding successfully in areas occupied by dingoes. Synthesis and applications . Our findings indicate that feral cats can coexist with dingoes, without apparent suppression of cat activity, abundance or fitness. Proposals to reintroduce or restore dingoes and other large predators to suppress invasive mesopredators and conserve biodiversity should be carefully evaluated on a site‐by‐site basis, as their ability to suppress cats and protect species of conservation significance will likely be context dependent. Abstract : The introduced dingo has been proposed as a novel way to suppress the impacts of introduced feral cats, thereby helping to conserve biodiversity in Australia. However scientific evidence of the dingo's ability to suppress feral cat activity is equivocal. Our study reveals that despite assertions to the contrary, dingoes did not suppress the spatial or temporal activity of feral cats. Cats not only coexisted with dingoes, they remained abundant, active and widespread across the landscape. Dingoes did not appear to structure ecosystems to create predation refuges for cat‐susceptible species. We suggest that proposals to restore or reintroduce apex predators such as dingoes to conserve biodiversity should be carefully evaluated on a site‐by‐site basis, as their ability to suppress cats and protect species of conservation significance will likely be context dependent. Editor's Choice